Online Identification and Verification of the Elastic Coupling Torsional Stiffness - Wanyou Li; Zhuoye Chai; Mengqi Wang; Xinhuan Hu; Yibin Guo (Shock and Vibration)
To analyze the torsional vibration of a diesel engine shaft, the torsional stiffness of the flexible coupling is a key kinetic parameter. Since the material properties of the elastic element of the coupling might change after a long-time operation due to the severe working environment or improper use and the variation of such properties will change dynamic feature of the coupling, it will cause a relative large calculation error of torsional vibration to the shaft system. Moreover, the torsional stiffness of the elastic coupling is difficult to be determined, and it is inappropriate to measure this parameter by disassembling the power unit while it is under normal operation. To solve these problems, this paper comes up with a method which combines the torsional vibration test with the calculation of the diesel shafting and uses the inherent characteristics of shaft torsional vibration to identify the dynamic stiffness of the elastic coupling without disassembling the unit. Analysis results show that it is reasonable and feasible to identify the elastic coupling dynamic torsional stiffness with this method and the identified stiffness is accurate. Besides, this method provides a convenient and practical approach to examine the dynamic behavior of the long running elastic coupling.